Delineation of pulmonary airway fluid protein fractions with HRPObinding-avidity by far-Western ligand blot and mass spectrometryanalyses: a model methodology for detecting mannose-bindingprotein expression profiles - Coyne, C. P.; Rashmir-Raven, A.; Jones, T.; Mochal, et al., C. (Acta Biomedica Atenei Parmensis, 2009)
Background and aim of work: Limited research to date has characterized the potential for HRPO to function as a primary molecular probe. Methods: Pulmonary airway fluid was developed by non-reducing far-Western (ligand) blot analyses utilizing conjugated HRPO-strepavidin or non-conjugated HRPO without the presence of primary immunoglobulin. Endogenous esterase-like biochemical activity of fractions within pulmonary airway fluid was inactivated to determine if they were capable of biochemically converting HRPO chemiluminescent substrate. Complementary analyses modified pulmonary fluid and HRPO with β-galactosidase and α-mannosidase respectively, in addition to determining the influence of mannose and maltose competitive binding on HRPO far-Western (ligand) blot analyses. Identification of pulmonary fluid fractions detected by HRPO far-Western blot analyses was determined by mass spectrometry. Results: Modification of pulmonary fluid with β-galactosidase, and HRPO with α-mannosidase in concert with maltose and mannose competitive binding analyses altered the intensity and spectrum of pulmonary fluid fractions detected by HRPO far-Western blot analysis. Identity of pulmonary airway fluid fractions detected by HRPO far-Western (ligand) blot analysis were transferrin, dynein, albumin precursor, and two 156 kDa equine peptide fragments. Conclusions: HRPO can function as a partially-selective primary molecular probe when applied in either a conjugated or non-conjugated form. Some protein fractions can form complexes with HRPO through molecular mechanisms that involve physical interactions at the terminal α-mannose-rich regions of HRPO glycan side-chains. Based on its known molecular composition and structure, HRPO provides an opportunity for the development of diagnostics methodologies relevant to disease biomarkers that possess mannose-binding avidity.